Makepung Tradition: Think Talk Write Learning Model and its Impact on the Short Story Writing Skills - Paramitha, Ni Luh Putu Ayu Eka Sri; Parmiti, Desak Putu; Riastini, Putu Nanci (Universitas Pendidikan Ganesha, 2024)
Lack of selection of innovative learning models, instilling cultural values ​​in learning materials, and difficulty developing student ideas. A learning model with cultural involvement is needed to develop students' ideas in writing to overcome these problems. This study examines the effect of the learning model Think Talk Write (TTW), which is tradition-oriented Makepung, on fifth-grade elementary school students' short story writing skills. This research includes quasi-experimental research (like an experiment) by design, and there is no equivalent post-test-only control group design. The research population was fifth-grade elementary school students, totaling 106 people. Samples are taken using random sampling, with 24 people as the experimental group and 21 as the control group. The data collection method uses written product assessment in the form of short stories, and the research instrument uses a multilevel scale model performance observation sheet. Research data were analyzed using descriptive statistics and inferential statistics (t-test). Based on the analysis of the t-test results, the sig. (2-tailed) namely 0.004 < 0.05. This research concludes that the learning model TTW tradition orientedMakepung is more influential on students' short story writing skills. This research aims to develop ideas, increase cultural values, encourage students to learn actively, and improve their writing skills.